Localizing the replication origin region on the physical map of the Mycoplasma capricolum genome. - Miyata, M (1993)
Four lines of evidence argue that the replication origin of the Mycoplasma capricolum genome lies within the 46-kb BamHI fragment bordered by two BamHI sites of the total of nine BamHI sites that have been located on the physical map (M. Miyata, L. Wang, and T. Fukumura, FEMS Microbiol. Lett. 79:329-334, 1991). First, this fragment lost its labeling in preference to other fragments when log-phase cultures were incubated in the presence of chloramphenicol for various times to inhibit the initiation of new rounds of replication and then further incubated with radioactive dTMP to allow DNA elongation to continue. Second, the relative frequencies of various restriction fragments of the genome DNA from exponentially growing cells decreased with increasing distance from the putative origin. Third, preferential labeling occurred when radioactive dTMP was added to cultures of a DNA elongation-defective, temperature-sensitive mutant with a simultaneous temperature downshift. Fourth, the M. capricolum homolog of the dnaA gene, which is located near the replication origin in many other bacteria, was found in the 46-kb fragment.